2016
DOI: 10.1111/apha.12728
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress‐induced angiogenesis in mouse muscle is independent of the vasodilator mechanism and quickly reversible

Abstract: AimIs modulation of skeletal muscle capillary supply by altering blood flow due to a presumptive shear stress response per se, or dependent on the vasodilator mechanism?MethodsThe response to four different vasodilators, and cotreatment with blockers of NO and prostaglandin synthesis, was compared. Femoral artery blood flow was correlated with capillary‐to‐fibre ratio (C:F) and protein levels of putative angiogenic compounds.ResultsAll vasodilators induced a similar increase in blood flow after 14 days, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 87 publications
0
19
0
1
Order By: Relevance
“…6 This angiogenic response appears to be independent of the vasodilator used to elevate shear stress. 36 In a previous study, we examined the effect of 4-week regular passive leg movement on muscle capillarization and found a small, but significant increase in capillary supply. 9 Passive leg movement induces an approximate twofold-to threefold increase in blood flow, but also a 20% passive stretch of the muscle, 34 and thus, the effect of shear stress vs. stretch on angiogenesis could not be fully distinguished in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This angiogenic response appears to be independent of the vasodilator used to elevate shear stress. 36 In a previous study, we examined the effect of 4-week regular passive leg movement on muscle capillarization and found a small, but significant increase in capillary supply. 9 Passive leg movement induces an approximate twofold-to threefold increase in blood flow, but also a 20% passive stretch of the muscle, 34 and thus, the effect of shear stress vs. stretch on angiogenesis could not be fully distinguished in this model.…”
Section: Discussionmentioning
confidence: 99%
“…28 Canonical sprouting angiogenesis is likely responsive to the local metabolic environment and as such is expected to produce a more homogeneous distribution of capillaries relative to the basal condition, whereas the lack of a myocyte response to hyperaemia would suggest a more stochastic angiogenic response, expected to result in an increased capillary supply of similar spatial distribution to that seen prior to intervention. 3,36 Capillary anisotropy (vessel orientation with respect to fibre axis) is dependent on the growth process recruited: abluminal sprouting in response to myocyte signalling will tend to place new vessels according to locations that will alleviate metabolic stress, 37 and hence reduce the heterogeneity of capillary spacing. In contrast, shear stress-induced angiogenesis leads to luminal division, producing vessels with the same orientation as parent vessels and hence maintains the orientation.…”
Section: Discussionmentioning
confidence: 99%
“…As cell alignment and network formation require cytoskeletal reconstruction, it has been concluded that the flow rates may have been too low to trigger shear stress sensing mechanisms and activate flow‐mediated angiogenesis. Continuous flow stimulation was also found to be required not only to maintain vessel sprouting, but to prevent rapid retraction …”
Section: The Mechanical Environment Of Angiogenesismentioning
confidence: 99%
“…Continuous flow stimulation was also found to be required not only to maintain vessel sprouting, but to prevent rapid retraction. 6,9 There are limitations to be considered in the in vitro models used for shear stress studies. For example, while angiogenesis can occur through sprouting (the migration of EC into tissue toward an angiogenic stimulus) and splitting (the separation of existing vessels by reorganization of EC), most in vitro models focus on the former.…”
Section: Shear Stress and Angiogenesismentioning
confidence: 99%
“…Recent work provided evidence that blood flow is an effective modulator of capillary growth and regression within the skeletal muscle of healthy adult rats, demonstrating that a sustained elevation in blood flow induced capillary growth and that return of blood flow to basal levels provoked capillary loss (Egginton et al. ). Extending this observation, our data suggest that the extent of capillary rarefaction that occurs under pathological conditions such as systemic hypertension (Chen et al.…”
Section: Discussionmentioning
confidence: 99%